2010
DOI: 10.1158/1535-7163.mct-10-0258
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Treatment Induces a Transient Increase in Tumorigenic Potential Associated with High Interleukin-6 Expression in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is characterized by the 5-year survival rate of ∼50%. Despite aggressive surgical, radiation, and chemotherapeutic interventions, 30% to 40% of patients die from the development of recurrent or disseminated disease that is resistant to chemotherapy. As a model of recurrence, we examined the effects of cisplatin on the ability of head and neck cancer cells to initiate tumors in a xenotransplant model. HNSCC cells were treated in vitro with cisplatin at a concentrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…This was based on Target scan and miRBase Targets database, which showed that IL-6 is potential target of let-7c, and also on previous finding of IL-6 as a putative let-7 target (18). In addition, a recent study has shown that IL-6 is released by genotoxic chemotherapy to protect cancer cell from cell death (19). First, we showed that cisplatin activated IL-6 mRNA in esophageal cancer cells (Fig.…”
Section: Cisplatin Activates Il-6/stat3 Prosurvival Signaling Pathwaymentioning
confidence: 64%
“…This was based on Target scan and miRBase Targets database, which showed that IL-6 is potential target of let-7c, and also on previous finding of IL-6 as a putative let-7 target (18). In addition, a recent study has shown that IL-6 is released by genotoxic chemotherapy to protect cancer cell from cell death (19). First, we showed that cisplatin activated IL-6 mRNA in esophageal cancer cells (Fig.…”
Section: Cisplatin Activates Il-6/stat3 Prosurvival Signaling Pathwaymentioning
confidence: 64%
“…This would result in the expansion of drug-resistant clonal variants during the 4-week drug treatment. Therefore, we examined the effect of LBH589 or BEZ235 treatment on cell viability of clonal variants of the Detroit 562 HNSCC cell line (Cameron et al , 2010; Poth et al , 2010) (Figure 5F). The results indicate that some clones are sensitive to BEZ235 whereas other clones are insensitive (Figure 5F).…”
Section: Resultsmentioning
confidence: 99%
“…However, we observed a generalised, yet incomplete, antitumour response to PI3KI treatment, which would be consistent with a submaximal dose of PI3KI being achieved in vivo . With respect to the presence of clonal variants within tumours, we have recently shown that HNSCC cell lines contain clonal variants that differ in their transcriptomic signature, their tumourogenic potential and their sensitivity to cisplatin (Cameron et al , 2010; Poth et al , 2010). Significantly, we have also shown that these clonal variants exist in human SCCs in situ (Cameron et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin and radiation have long been the backbone and standard of care of HNSCC patients presenting with locally advanced disease. Cisplatin-based chemotherapy and radiation have already been shown to induce IL-6 secretion (41, 42) implying that EGFRI-induced IL-6 may not be unique to EGFR inhibitors. It is possible that the cell death caused by standard chemo-/radiotherapy in HNSCC may be activating pathways leading to IL-6 and other pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%